2014
DOI: 10.2147/cia.s67200
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Thai version of the Diabetes Distress Scale in diabetic seniors

Abstract: BackgroundThe Diabetes Distress Scale (DDS) is an important measure of diabetes-related emotional distress that has been widely used in the Western world. In Thailand, there is a lack of reliable and valid scales for assessing distress levels in diabetes patients, specifically in older adults.ObjectivesThe main objectives of this study were to adapt the DDS for use in Thai diabetic elderly and to evaluate its psychometric properties.MethodsThe 17-item DDS was linguistically adapted using forward–backward trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 27 publications
4
29
1
1
Order By: Relevance
“… proposed that the DDS2 is suitable for an initial screening of high diabetes‐specific emotional distress in clinical consultations, and showed that DDS2 was significantly associated with HbA 1c levels. The DDS2 consists of items from the regimen‐related distress and emotional burden subscales and a recent study found that items of regimen‐related distress and emotional burden loaded on the same factor . In the present study the DDS2 showed a significant relationship with follow‐up HbA 1c , but not when adjusting for baseline glycaemic control.…”
Section: Discussioncontrasting
confidence: 43%
“… proposed that the DDS2 is suitable for an initial screening of high diabetes‐specific emotional distress in clinical consultations, and showed that DDS2 was significantly associated with HbA 1c levels. The DDS2 consists of items from the regimen‐related distress and emotional burden subscales and a recent study found that items of regimen‐related distress and emotional burden loaded on the same factor . In the present study the DDS2 showed a significant relationship with follow‐up HbA 1c , but not when adjusting for baseline glycaemic control.…”
Section: Discussioncontrasting
confidence: 43%
“…Total DRD, EB, and RD were found to be associated with both HbA1C and co-morbidity. EB includes a variety of negative emotions such as despair, conflict and fear-induced anger that result from thinking about the prospect of a lifetime of living with diabetes, and feeling overwhelmed by the many resulting demands [20]. Type D personality [46] and alexithymia [47] have been reported to adversely affect outcomes in patients with T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…The Diabetes Distress Scale (DDS-17) questionnaire for assessing DRD developed by Polonsky et al [37] was translated into the Thai language by Kattika [20]. The alpha coefficient of the questionnaire was 0.95.…”
Section: Data Collection and Diabetes-related Distress Level Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes distress, an affective disorder, is a syndrome comprised of a multidimensional component, such as worry, conflict, frustration, and discouragement that can accompany living with diabetes, and is closely related to depression [5]. Majority of people with diabetes who were depressed experienced diabetes distress, however, most of those experiencing diabetes distress were not depressed [6].…”
Section: Introductionmentioning
confidence: 99%